REVIEW OF SHARIA ECONOMIC LAW ON STAPLE STOMACHING - Fira Salsabila Zuhra; Ida Friatna; Nahara Eriyanta (JURISTA: Jurnal Hukum dan Keadilan, 2021)
In Islam iḥtikār, namely the hoarding of goods is not justified due to the act of controlling the market in such a way that it can damage the existing market mechanism with a type of goods controlled by the person concerned, so that he can control the price at will by hoarding it (holding it). In reality, this activity is practiced among traders in the Trienggadeng market, as a result of which basic commodities are scarce on the market which is followed by soaring commodity prices for basic commodities. The formulation of the research problem is how is the practice of hoarding staples carried out by traders in the Trienggadeng market, what are the factors for hoarding staples by traders, and how is the review of sharia economic law towards the practice of hoarding staples by traders. This study uses a type of descriptive qualitative research analysis with data collection techniques through interviews and documentation. The results of the study show that the practice of hoarding goods in the Trienggadeng market is carried out when merchandise stocks are running low. Groceries traders sell goods at twice the normal price and even increase 100% of the previous price on the grounds that there is no means of transportation to transport the community's needs. The factor in the hoarding of staple goods is because the stock of merchandise on the market is running low, and also due to the factor that goods are rare and difficult to obtain so that buyers buy up goods for their own needs, and traders buy up goods needed by the community to stock goods sold for their needs and profits. So that the Fiqh scholars do not allow iḥtikār because every act of persecution including iḥtikār is forbidden by other. religions.